Zad 1
a) - 7 +Y + 9 + 2Y =
b) X - 3X + 2 - 2X - 7 =
c) - 5x + 4Y - Y - 7X - 9Y =
d) 4X + 5 - X - 4 + x - 3X =
e) 0,5A - 2A + 9 - 0,5A - 11,5 =
f) - 14K + 9K - 13 + K + 3 + 4K =
g) - 3K + 2M + 5M - 7 + K - M =
h) 2X - 4 + 3X - 2 =
i) X - 3Y - 2X + 6Y =
j) 2Y - 5 - 3Y - 4 - 8Y + 9 =

Plisss !!
Mam to na jutro !!!
Daję najjj !!

3

Odpowiedzi

2010-03-08T19:06:35+01:00
A) - 7 +Y + 9 + 2Y = 3Y+2
b) X - 3X + 2 - 2X - 7 = -4x - 5
c) - 5x + 4Y - Y - 7X - 9Y = -6Y -12X
d) 4X + 5 - X - 4 + x - 3X = 1+X
e) 0,5A - 2A + 9 - 0,5A - 11,5 = 2A+2,5
f) - 14K + 9K - 13 + K + 3 + 4K = -10
g) - 3K + 2M + 5M - 7 + K - M =-2K+7M-7
h) 2X - 4 + 3X - 2 =6X-6
i) X - 3Y - 2X + 6Y =3Y-X
j) 2Y - 5 - 3Y - 4 - 8Y + 9 =-7Y


Najlepsza Odpowiedź!
2010-03-08T19:07:59+01:00
A) - 7 +Y + 9 + 2Y = 2 + 3Y
b) X - 3X + 2 - 2X - 7 = -5x -5
c) - 5x + 4Y - Y - 7X - 9Y =-12X + -6Y
d) 4X + 5 - X - 4 + x - 3X =1X -1
e) 0,5A - 2A + 9 - 0,5A - 11,5 =-2A -2,5
f) - 14K + 9K - 13 + K + 3 + 4K = 0K -10= -10
g) - 3K + 2M + 5M - 7 + K - M =-2K + 6M -7
h) 2X - 4 + 3X - 2 =5X -6
i) X - 3Y - 2X + 6Y = -1X +3Y
j) 2Y - 5 - 3Y - 4 - 8Y + 9 =-9Y + 0= 9Y
2010-03-08T19:09:22+01:00
A) - 7 +Y + 9 + 2Y =2 + 3Y
b) X - 3X + 2 - 2X - 7 = -4X -5
c) - 5x + 4Y - Y - 7X - 9Y = - 12x - 6Y
d) 4X + 5 - X - 4 + x - 3X = 1 + 1x
e) 0,5A - 2A + 9 - 0,5A - 11,5 = -2A -2,5
f) - 14K + 9K - 13 + K + 3 + 4K = 10
g) - 3K + 2M + 5M - 7 + K - M = 2K + 6M -7
h) 2X - 4 + 3X - 2 = 5X -6
i) X - 3Y - 2X + 6Y = X + 3Y
j) 2Y - 5 - 3Y - 4 - 8Y + 9 =-9Y